Delta-1 Activation of Notch-1 Signaling Results in HES-1 Transactivation - Jarriault, Sophie (American Society for Microbiology, 1998)
The Notch receptor is involved in many cell fate determination events in vertebrates and invertebrates. It has been shown in Drosophila melanogaster that Delta-dependent Notch signaling activates the transcription factor Suppressor of Hairless, leading to an increased expression of the Enhancer of Split genes. Genetic evidence has also implicated the kuzbanian gene, which encodes a disintegrin metalloprotease, in the Notch signaling pathway. By using a two-cell coculture assay, we show here that vertebrate Dl-1 activates the Notch-1 cascade. Consistent with previous data obtained with active forms of Notch-1 a HES-1-derived promoter construct is transactivated in cells expressing Notch-1 in response to Dl-1 stimulation. Impairing the proteolytic maturation of the full-length receptor leads to a decrease in HES-1 transactivation, further supporting the hypothesis that only mature processed Notch is expressed at the cell surface and activated by its ligand. Furthermore, we observed that Dl-1-induced HES-1 transactivation was dependent both on Kuzbanian and RBP-J activities, consistent with the involvement of these two proteins in Notch signaling in Drosophila. We also observed that exposure of Notch-1-expressing cells to Dl-1 results in an increased level of endogenous HES-1 mRNA. Finally, coculture of Dl-1-expressing cells with myogenic C2 cells suppresses differentiation of C2 cells into myotubes, as previously demonstrated for Jagged-1 and Jagged-2, and also leads to an increased level of endogenous HES-1 mRNA. Thus, Dl-1 behaves as a functional ligand for Notch-1 and has the same ability to suppress cell differentiation as the Jagged proteins do.